AN ANALYSIS OF DISCOURSE STRUCTURE OF TEXT IN CIRCULAR LETTER ABOUT THE RULES IN TERMINAL UMUM DABN PELABUHAN PROBOLINGGO - Luthfie, Afrizky Karlina; Tjahyadi, Indra; Andayani, Sri; Wafa, Hosnol (JURNAL LITERASI, 2024)
The port is a work area that has a high level of work risk in its operation. PT. Delta Artha Bahari Nusantara as the operator of Terminal Umum DABN Pelabuhan Probolinggo issued circular letter about the rules to protect the environment, workers and smooth port activities, it is necessary to have rules and regulations at the port. This study interesyed to analyze the text structure of Circular Letter About The Rules In Terminal Umum DABN Pelabuhan Probolinggo to see about the macro structure, superstructure, and micro structure that consist in the text in circular letter. This study theory uses critical discourse analysis with the Van Dijk model. This study uses a descriptive qualitative approach in analyzing the problem. The research was conducted using the critical discourse analysis method, so that study can understand how PT. Delta Artha Bahari Nusantara issued Surat Edaran Tentang Tata Tertib Di Lingkungan Kerja Terminal Umum DABN Pelabuhan Probolinggo by analyzing the text in the circular letter. The design use in this study is qualitative research. The data source of this research is text form of the circular letter about the rules in Terminal Umum DABN Pelabuhan Probolinggo. Terminal Umum DABN Pelabuhan Probolinggo is the location for collecting data using documentation. The several steps in writing the analysis of this study is make a data classification and interpretation then re-checking to get the validation. The data analysis description method of the study is informal. The discourse structure contained in the text of circular letter will explain the macro structure, superstructure and micro structure in terms of thematic, schema and semantic analysis also finding the coherences that consist in the text of Surat Edaran Tentang Tata Tertib Di Lingkungan Kerja Terminal Umum DABN Pelabuhan Probolinggo.